Carte Postale Ancienne Paris 17 - unknown, in the public domain (NC, 2026)
Postal Card - beginning of 20th century, Paris 17th arrondissement
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons